NEUROMARKETING TECHNOLOGIES IN BRAND STRATEGY FORMATION: EPISEOOLOGICAL FUNDAMENTALS - DANYLYUK, ANNA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of this work is to analyze neuromarketing technologies and their application in the formation of brand strategy. Today, neuromarketing is a new area of marketing research based on neurobiology, psychology and marketing. This combination helps marketers to investigate how physiologically the human brain is affected by advertising, marketing strategy. Neuromarketing uses a variety of tools such as: electroencephalography, magnetic resonance imaging, functional magnetic resonance imaging, magnetic encephalography, iTracking, voice pitch analysis, facial recognition, skin galvanic response, positron emission tomography, positron emission tomography and other. These tools are used effectively in creating a brand strategy and advertising campaign, as they can learn about the intentions of customers, and as a result, the marketer can create a strong, favorable and positive brand image in the minds of buyers to activate emotions, which in turn lead before the purchase decision. Neuromarketing technologies take the formation of brand strategy to a new level, as they allow you to create marketing materials that find a response in the audience. Just as most consumers associate certain emotions and mental images with brands, they can create or spoil the impression of a product or campaign. During research, it was found that the success of a marketing strategy depends on forecasting demand and customer preferences. Therefore, most companies use neuromarketing to determine how people make decisions. A positive brand image activates the emotional brain, which transmits information to the rational brain, changing perceptions of it. Marketers need to create a strong and reliable image in the minds of target customers through marketing strategy. Therefore, if marketers use neuromarketing technologies, they will maximize the benefits and create a win-win situation for both parties.